Assessment of Trace Metal Distribution and Contamination In Surface Soils of Al-Waziriya, Baghdad - Muna Aziz Rahi; Mahmood .R.M. Al-Qaysi; Abdul Hameed M.J. al Obaidy (Engineering and Technology Journal, 2014)
A total of 100 samples from the top soil were collected from four different zones (tow industrial locations, tow residential locations) located in Al-Waziriya, Baghdad. Soil samples were analyzed for their content of Cd, Cu, Pb and Zn. A profile for average content of these selected metals has been determined by taking average values for different zones. The average concentrations of Cd, Cu, Pb and Zn in the whole area were 11.45, 143.3, 3291.38 and 195.2 mg/kg, respectively. Highest concentrations for selected heavy metals were observed in the industrial area. Enrichment factor calculations indicated that Pb, Cu, Cd and Zn are highly enriched. Battery factories, fossil fuel combustion from traffic emissions, wear of brake lining materials, and several industrial processes are considered as major sources of the studied heavy metals.